Galectin-3 Mediates Thrombin-Induced Vascular Smooth Muscle Cell Migration - Tian, Lei; Huang, Chun-Kai; Ding, Fenghua; Zhang, Ruiyan (Frontiers in Cardiovascular Medicine, 2021)
VSMCs migration is an important step in the progression and development of vulnerable plaques. Thrombin is involved in both physiological and pathological processes of atherosclerosis. Therefore, the elucidation of the mechanisms underlying thrombin-induced VSMCs migration is essential for devising effective treatments aimed to the prevention of plaque instability. In this study, we found that thrombin activated MAPK signaling pathways and increased the expression of galectin-3 which was also a well-known factor in atherosclerosis. Knockdown of galectn-3 by specific small interfering RNA (siRNA) blocked thrombin-induced activation of ERK1/2 and p38 MAPK, but not JNK MAPK. Src/FAK phosphorylation was also shown to be activated by thrombin. FAK autophosphorylation at Y397 was most significantly inhibited by galectin-3 siRNA. Galectin-3 siRNA or specific inhibitor (P38 MAPK inhibitor, ERK1/2 inhibitor) effectively prevented thrombin-induced VSMCs migration via reducing paxillin expression. These findings demonstrate, for the first time, that thrombin stimulation of VSMCs migration and paxillin expression are regulated by galectin-3, and ERK1/2, p38 MAPK and Src/FAK signaling pathways are involved in this process. These results are beneficial to clarify the role of galectin‑3 in thrombin-induced advanced lesions in atherosclerosis and shed new insights into the regulatory mechanism of VSMCs migration in combating plaque rupture.